2015
DOI: 10.1159/000374062
|View full text |Cite
|
Sign up to set email alerts
|

MiR-31 Downregulation Protects Against Cardiac Ischemia/Reperfusion Injury by Targeting Protein Kinase C Epsilon (PKCe) Directly

Abstract: Background: Various miRNAs have been shown to participate in cardiac ischemia/reperfusion injury (I/R). miR-31 was identified as the most strikingly upregulated miRNA after acute myocardial infarction; therefore, the underlying role and mechanism of miR-31 in cardiac I/R was investigated. Methods: miR-31 expression was detected after cardiac I/R in mice. The cardioprotective effect of miR-31 downregulation was assessed in vitro and in vivo. The functional target gene and its downstream molecule were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…In addition, we further showed that downregulation and upregulation of miR-199a-5p mRNA by transfection respectively increased and decreased GSK-3β both in mRNA and protein levels suggesting that miR-199a-5p mRNA exert its effects via GSK-3β. It is noteworthy to mention that other microRNAs, such as miR-31 [32] and miR-17 [33], have also been found to be involved in cardiac ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we further showed that downregulation and upregulation of miR-199a-5p mRNA by transfection respectively increased and decreased GSK-3β both in mRNA and protein levels suggesting that miR-199a-5p mRNA exert its effects via GSK-3β. It is noteworthy to mention that other microRNAs, such as miR-31 [32] and miR-17 [33], have also been found to be involved in cardiac ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…The myocardial infarct size was measured as previously described [14]. Immediately following reperfusion, the LAD was ligated completely and 4 mL of 1% Evans blue dye was injected retrogradely into the aorta to delineate the region of myocardial perfusion.…”
Section: The Determination Of the Infarct Sizementioning
confidence: 99%
“…Moreover, an accumulating number of miRNAs have been verified to be critically involved in maintaining normal heart function and pathological process involved in cardiovascular diseases [11][12][13][14][15][16][17]. In addition to being potent regulators of gene expression, recent studies have shown that miRNAs may also serve as circulating biomarkers for various diseases, including tumors and cardiovascular disorders, because of their remarkable stability in the blood, urine and other fluids [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%